Research of the Stiffness Identification and Error Compensation of Industrial Robot Under Heavy Load - Wang Xu; Li Dongsheng; Wang Mingming (Jixie chuandong)
Intends to accurately identify joint stiffness parameters of industrial robot under heavy load condition,firstly,dexterity of the robot in joint space and workspace is determined based on the Frobenius norm of Jacobian matrix,then,the integrated model of load and robot are built by using equivalent torque method,and finally,a deformation error compensation method by directly calculating joint deformation and compensating is put forward. The laser tracker and ABB IRB 6 640 robot are used to conduct kinematic error compensation experiment,joint stiffness identification experiment and joint deformation compensation experiment. The results show this method can effectively compensate joint deformation and thus improve the absolute accuracy of the robot. The positioning error of the robot is significantly reduced from 0. 694 mm to 0. 230 mm,with an accuracy improvement by roughly 67%.